Fighting words individuals, communities, and liberties of speech - Greenawalt, Kent 1936- (Princeton Univ. Press, 1995)
For a number of purposes, Greenawalt finds it instructive to compare U.S. and Canadian jurisprudence. He points out, for instance, that the theory under which the Canadian Supreme Court supports suppression of obscenity is strikingly in line with the claims of those feminists who regard obscenity as a major evil: equality, especially the aspirations to equality of groups victimized in the past, rates highly as a constitutional value in Canada. In addition to discussing the sometimes conflicting claims of those seeking freedom of speech and those working to promote equality and protect citizens from oppression, Greenawalt looks at what speech does as well as what it says. He also compares the importance of the motive of the speaker to the actual effect of speech on its audience